2017
DOI: 10.1155/2017/2629310
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and Autonomic Regulation of Response to Sensory Stimuli among Children: A Systematic Review of Relationship and Methodology

Abstract: Background Previous studies have explored the correlates of behavioural and autonomic regulation of response to sensory stimuli in children; however, a comprehensive review of such relationship is lacking. This systematic review was performed to critically appraise the current evidence on such relationship and describe the methods used in these studies. Methods Online databases were systematically searched for peer-reviewed, full-text articles in the English language between 1999 and 2016, initially screened b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 56 publications
(248 reference statements)
1
22
0
Order By: Relevance
“…First, the multiple reactivities and patterns of arousal should be studied in a more complex and coordinated manner. However, in line with earlier reviews (e.g., Rogers and Ozonoff, 2005;Gomez et al, 2017), we highlight the variability in children's ANS-HPA axis responses to sensory stimuli, regardless of diagnosis. We view this heterogeneity as a natural and expected continuum of arousal occurring across individual nervous systems.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…First, the multiple reactivities and patterns of arousal should be studied in a more complex and coordinated manner. However, in line with earlier reviews (e.g., Rogers and Ozonoff, 2005;Gomez et al, 2017), we highlight the variability in children's ANS-HPA axis responses to sensory stimuli, regardless of diagnosis. We view this heterogeneity as a natural and expected continuum of arousal occurring across individual nervous systems.…”
Section: Resultssupporting
confidence: 89%
“…Gatzke- Kopp and Ram, 2018). It is predominantly used to capture variability in physiological sympathetic arousal in the SMD literature (Gomez et al, 2017). Generally, greater frequency and magnitude of EDA to either all or specific sensory stimulation was observed in the SNS-focused SMD studies reviewed, illustrating that these temporal dimensions were recurrent regardless of diagnosis (see Table 2).…”
Section: Modes Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence that supports autonomic regulation of response to sensory stimuli stemmed out from a series of research that hypothesizes differences in PNS or SNS functions in response to a laboratory paradigm that presents a series of sensory stimuli among children with and without known problems in the regulation of response toward sensory stimuli. In a systematic review that explores the extant literature in the behavioral and physiological regulation of response to sensory stimuli among children, Gomez et al [ 43 ] have suggested methodological inconsistencies. For instance, the prevalent use of a single autonomic physiological measure was commonly observed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of a multidomain sensory paradigm may not always be suitable. Our recent literature review urges the use of modality-specific measurements to improve the sensitivity of measures [ 43 ]. The auditory modality seems to offer a more sensitive stimulus to elicit physiological responses [ 6 , 50 ].…”
Section: Introductionmentioning
confidence: 99%